1956
DOI: 10.1149/1.2430309
|View full text |Cite
|
Sign up to set email alerts
|

High Pressure Oxidation of Metals—Tungsten in Oxygen

Abstract: Tungsten rod and sheet were found to oxidize linearly in oxygen from 600 ~ to 850~ at oxygen pressures ranging from 20 to 500 psia. Oxidation rate increased with increased oxygen pressure at temperatures 750~176Theoretical considerations indicate that an equilibrium adsorption process occurs prior to the rate-determining step. The assumption of a linear change of adsorption energy with increase of surface coverage Mlowed observed oxidation rates to be corrected for pressure effect. The activation energy was 48… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

1961
1961
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 10 publications
2
10
0
Order By: Relevance
“…During this set of experiments, it was found that some of the formed tungsten oxide sublimes. This phenomena was previously observed in the same temperature range by Gulbransen and Andrew [23] and Baur et al [24]. During experimentation some of the volatilized tungsten oxide was deposited on the reactor walls forming a yellowish thin film.…”
Section: Tungsten Bars Oxidation At 800°csupporting
confidence: 80%
“…During this set of experiments, it was found that some of the formed tungsten oxide sublimes. This phenomena was previously observed in the same temperature range by Gulbransen and Andrew [23] and Baur et al [24]. During experimentation some of the volatilized tungsten oxide was deposited on the reactor walls forming a yellowish thin film.…”
Section: Tungsten Bars Oxidation At 800°csupporting
confidence: 80%
“…These authors have also developed Eq. 1 which represents experimental rates within a factor of two for After Baur et al [8] and GulbraI_sen et al [9]. The conditions encompassed in this study appear to be the ones most likely experienced in accident scenarios for fusion reactors.…”
Section: Review Of Oxidation Processesmentioning
confidence: 80%
“…The differences in the values of coefficients of the chemical diffusion and diffusion activation energy, obtained by both thermogravimetry and the measuring of the electrical conductivity, could be due to the different mobility of singly ionized copper vacancies and electroneutral vacancies. Similarly, studies of the kinetics of the oxidation of copper, performed by several authors [16,[65][66][67][68][69][70][71], indicate that the transport of matter in the oxide scale could be described by a simple mechanism of upward diffusion of copper ions through electroneutral copper vacancies (with the exponent in the parabolic dependence of the oxidation rate on p O 2 being around 1/4). Wagner Grünewald [16] and Haugsrud and Kofstad [71] obtained the exponent of about 1/ 7 at lower oxygen pressures, indicating a complex structure and transport of matter during the growth of the oxide scale.…”
Section: Introductionmentioning
confidence: 97%